2012
DOI: 10.15288/jsad.2012.73.834
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Recruitment Using Online Networks: Lessons Learned From an Online Study of Alcohol and Other Drug Use Utilizing a Web-Based, Respondent-Driven Sampling (webRDS) Strategy

Abstract: We used a web version of Respondent-Driven Sampling (webRDS) to recruit a sample of young adults (ages 18-24) and examined whether this strategy would result in alcohol and other drug (AOD) prevalence estimates comparable to national estimates (National Survey on Drug Use and Health [NSDUH]). Method: We recruited 22 initial participants (seeds) via Facebook to complete a web survey examining AOD risk correlates. Sequential, incentivized recruitment continued until our desired sample size was achieved. After co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
174
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(182 citation statements)
references
References 14 publications
4
174
2
2
Order By: Relevance
“…However, increasing the number of seeds does not always work -the RAND study (Berry et al 2010) increased the number of seeds from five to 189 and still came up short. Except for this study, the number of seeds in Internet RDS studies tends to be much smaller with numbers ranging from nine (Wejnert and Heckathorn 2008) to 22 (Bauermeister et al 2012).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, increasing the number of seeds does not always work -the RAND study (Berry et al 2010) increased the number of seeds from five to 189 and still came up short. Except for this study, the number of seeds in Internet RDS studies tends to be much smaller with numbers ranging from nine (Wejnert and Heckathorn 2008) to 22 (Bauermeister et al 2012).…”
Section: Introductionmentioning
confidence: 69%
“…A study in a single college finished recruiting in a single weekend (Wejnert and Heckathorn 2008). Web recruiting for the drug and alcohol study at a single university (Bauermeister et al 2012) concluded after 2.5 months. Web recruiting for the study about men who have sex with men in Vietnam (Bengtsson et al 2012) took about two months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers, regardless of their constitution and efficiency, can only interview so many people in one day, interview locations are not available at all times, and respondents' schedules do not always correspond with researchers'. Web-based RDS (webRDS) eliminates many of the logistical problems (though introducing new and complicated replacements), and tends to increase the speed of sample gathering [34,36,37].…”
Section: Methodsmentioning
confidence: 99%
“…A primary drawback of webRDS, however, is that researchers are not able to meet with respondents face-to-face to confirm their status as attribute possessors (such as track marks for intravenous drug users) or to weed out respondents who provide fake responses in lieu of recruiting real people (to collect the recruitment reward)-though Bauermeister et al telephoned each prospective recruit to verify their existence and to protect from virtual ballot stuffing [37]. To counteract the selection of fraudulent respondents, Wejnert and Heckathorn suggest keeping recruitment re-wards small and tracking internet protocol (IP) identification numbers so that multiple responses cannot emanate from the same computer [34].…”
Section: Methodsmentioning
confidence: 99%